Role of microRNAs in breast cancer development and their potential as biomarkers - K. A. Grishina; V. A. Khaylenko; D. V. Khaylenko; A. V. Karpukhin (ABV-press, 2018)
Breast cancer is the 2nd most common malignant disease after lung cancer; about 1 in 8 women will develop breast cancer in her lifetime. Cancer progression is a serious complication of the disease that encourages comprehensive investigation of molecular mechanisms underlying breast cancer development. This is also important for healthcare professionals involved in patient management, since they have to choose an optimal treatment regimen. This article discusses the role of microRNAs in the development of breast cancer, their biogenesis, classification, association with various molecular subtypes of breast cancer, and their potential role in the development of new targeted drugs for breast cancer therapy. Current research on the role of microRNAs in breast cancer progression is focused on the development of markers for breast cancer prognosis, diagnostic markers and new targeted drugs.